Transformasi Energi Rumah Tangga: Otomatisasi Beban Listrik dengan IoT - Kiswantono, Agus (Universitas Lampung, 2025)
This study aims to develop an Internet of Things (IoT)-based electrical load control system that can improve energy consumption efficiency in households. The system utilizes the Blynk application connected to relays and current sensors to monitor and control electricity usage in real-time. The research compares the system with and without the use of a repeater to assess its impact on response time. The results show that the use of a repeater reduced the communication response time between the devices and the application from 4.2 seconds to 2.8 seconds. This reduction in response time allows the system to optimize load management more quickly and efficiently. Additionally, the system has the potential to reduce energy waste, lower electricity costs, and support efforts to reduce carbon emissions through better energy management. However, challenges include the initial investment costs, device compatibility, and data security issues, which need to be addressed for wider implementation in Indonesia. With further development, this system holds great potential in supporting energy sustainability and household efficiency.